Cooperation or Coopetition Strategy: What is the Best Strategy Face to Competition' Intensity and Strategic Capabilities? - Asma Zgarni (International Review of Management and Marketing, 2019)
This study aims to decide on the question of the supremacy of coopetition' strategies compared to pure cooperation' strategies according to two explanatory factors both internally and externally. Through a sample of Tunisian industrial firms, the study confirms the simultaneous effect of competitive intensity and strategic capabilities on the nature of the strategy adopted. However, face to competition' intensity, we conclude that strategic capabilities hold the highest weight in explaining coopetition and customer cooperation strategies, but the lowest weight when it comes to supplier cooperation. Also, we show the duality of recourse to the customer cooperation as well as the horizontal coopetition in front of the competition' intensification. Even more, face to excessive competitive intensity, we find, surprisingly, the primacy of recourse to customer cooperation in face to horizontal coopetition. Moreover, our results also show that the strong need for strategic capabilities accentuates the use of coopetition to the detriment of cooperation.